Effectiveness of Evaluation of 4th Year Students Basis for Enhanced Training Program in Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the effectiveness of training to enhance the trainingprogram of BSHM at Bestlink College of the Philippines.The respondents of this quantitative research are one hundred (50) students in the 4th year ofthe Bachelor of Science in Hospitality Management major in Hospitality Management atBestlink College of the Philippines. The results of this study reveal that the majority of therespondents are 30 students in their 4th year, mostly 18–22 years old, and 49% are single. Itreveals that leadership, meetings, incentives, conferences, exhibitions (M.I.C.E.), teamwork,and on-the-job training (OJT) are evaluated as "Very Effective" in terms of training. Financialproblems, lack of confidence, and communication skills are evaluated as "Very Effective" asthe most challenging for students to take their training.Based on the gathered data and conclusions drawn, this study recommends that theadministration and students actively participate in all the training and activities from schoolthat can help them reach their competency. The professor or instructor should assessstudents throughout the lesson and provide consistent one-on-one or small group interventionto meet the highest expectations.
Keywords: Hospitality Management